2013
DOI: 10.1007/s11084-013-9346-1
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Interplanetary Transfer of Microbes: Assessing the Viability of Deinococcus spp. Under the ISS Environmental Conditions for Performing Exposure Experiments of Microbes in the Tanpopo Mission

Abstract: To investigate the possible interplanetary transfer of life, numerous exposure experiments have been carried out on various microbes in space since the 1960s. In the Tanpopo mission, we have proposed to carry out experiments on capture and space exposure of microbes at the Exposure Facility of the Japanese Experimental Module of the International Space Station (ISS). Microbial candidates for the exposure experiments in space include Deinococcus spp.: Deinococcus radiodurans, D. aerius and D. aetherius. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 54 publications
2
41
0
1
Order By: Relevance
“…We have isolated Deinococcus aerius and Deinococcus aetherius, which are new species of Deinococcus, from air dust samples at the upper troposphere and lower stratosphere (Yang et al, 2008a(Yang et al, , 2009b(Yang et al, , 2010. Deinococcus aetherius forms cell aggregates during culture and exhibited higher resistance to UV than D. radiodurans and D. aerius (Yang et al, 2008a;Kawaguchi et al, 2013). The results suggest that the ability to form cell aggregates could be important for UV resistance at high altitude (Mancinelli and Klovstad, 2000;Horneck et al, 2001;Yang et al, 2008a;Smith et al, 2011).…”
Section: Interplanetary Transfer Of Cell Aggregatesmentioning
confidence: 96%
See 3 more Smart Citations
“…We have isolated Deinococcus aerius and Deinococcus aetherius, which are new species of Deinococcus, from air dust samples at the upper troposphere and lower stratosphere (Yang et al, 2008a(Yang et al, , 2009b(Yang et al, , 2010. Deinococcus aetherius forms cell aggregates during culture and exhibited higher resistance to UV than D. radiodurans and D. aerius (Yang et al, 2008a;Kawaguchi et al, 2013). The results suggest that the ability to form cell aggregates could be important for UV resistance at high altitude (Mancinelli and Klovstad, 2000;Horneck et al, 2001;Yang et al, 2008a;Smith et al, 2011).…”
Section: Interplanetary Transfer Of Cell Aggregatesmentioning
confidence: 96%
“…Our previous report indicated that in aggregates, deinococcal cells near the surface layer were killed by UV radiation, and the layers of killed cells protected the cells underneath from UV damage (Kawaguchi et al, 2013). Deinococcus radiodurans, D. aerius, and D. aetherius are estimated to survive after 1 year of exposure under vacuum, temperature changes, heavy ions, and c rays (Kawaguchi et al, 2013). Submillimeter deinococcal aggregates shield internal cells against the intense solar UV, and such cells survive the LEO environment for 1 year.…”
Section: Interplanetary Transfer Of Cell Aggregatesmentioning
confidence: 99%
See 2 more Smart Citations
“…TANPOPO (Sub-Theme 2) Kawaguchi et al (2013) have suggested the possible importance of cell-aggregate as an ark for terrestrial microbes to enable interplanetary transfer. The concept was named "massapanspermia hypothesis".…”
Section: B1 Survival I-iii Experimentsmentioning
confidence: 99%